Development and Validation of a Novel Mitochondrion and Ferroptosis-Related Long Non-Coding RNA Prognostic Signature in Hepatocellular Carcinoma - Xia, Wuzheng; Zeng, Cong; Zheng, Zehao; Huang, Chunwang; Zhou, Yu; Bai, Lan (Frontiers in Cell and Developmental Biology, 2022)
Mitochondrion and ferroptosis are related to tumorigenesis and tumor progression of hepatocellular carcinoma (HCC). Therefore, this study focused on exploring the participation of lncRNAs in mitochondrial dysfunction and ferroptosis using public datasets from The Cancer Genome Atlas (TCGA) database. We identified the mitochondrion and ferroptosis related lncRNAs by Pearson analysis and lasso-cox regression. Moreover, the Real-time quantitative reverse Transcription PCR (RT-qPCR) was utilized to further confirm the abnormal expression of these lncRNAs. Based on eight lncRNAs, the MF-related lncRNAs prognostic signature (LPS) with outstanding stratification ability and prognostic prediction capability was constructed. In addition, function enrichment analysis and immune cell infiltration analysis were performed to explore the possible functions of lncRNAs and its impact on tumor microenvironment. The pathways related to G2M checkpoint and MYC were activated and the infiltration ratio of T cells regulatory, Macrophages M0 and M2 were higher in high-risk group. In conclusion, these lncRNAs may affect mitochondria functions, ferroptosis and immune cells infiltration in HCC through the specific pathways, which may provide valuable insight into the progression and therapies of HCC.